Agências reguladoras e a efetivação da ordem econômica-constitucional brasileira: desafios da regulação em um cenário de intensificação do poder econômico nas relações sociais - Vilela, Danilo Vieira (2018)
This thesis analyzes the process of creation of the regulatory agencies, focusing on the transformation of the Brazilian Public Administration management models. It seeks to understand them not as a neutral instrument nor as a mechanism for implementing policies of a particular party or government. On the contrary, with the premise of questioning the notion of subsidiarity and, consequently, a proposal of a subsidiary State, the thesis seeks to highlight the role of regulatory agencies as instruments for the realization of the economic-constitutional order. The agencies will also be analyzed as a thermometer able to measure the way in which the relationship between law, politics and economics takes place, being examined if they provide effective limits to the influence of economic power. Without overlooking the economic phenomenon, but overcoming the traditional concept of homo economicus, in view of the insufficiency of the pure approach of the economic analysis of law, it will be argued that even if the agencies are supposed to have assumed "original sin", with a view to their creation and development in Brazil in a scenario of dismantling and weakening of the state, it is possible, however, that their operation be directed to a greater scope for the realization of sustainable national development. The objective is, in summary, based on a developmental perspective, to calibrate the functions of the agencies so that they are adequate to the proposal of a State that is concerned with a transformative development of the excluding structures, thus avoiding that they serve as a stage for captured actions, either by the market or even by the government. It is hoped, therefore, to rescue the importance of a State that promotes an inclusive and transforming economic development of the structures, which demands a re-reading of the agencies' functioning in the perspective of a Constitutional and Democratic State of Law.